ХРОНИЧЕСКАЯ СЕРДЕЧНАЯ НЕДОСТАТОЧНОСТЬ И АНЕМИЯ: РОЛЬ ДЕФИЦИТА ЖЕЛЕЗА И ЕГО КОРРЕКЦИЯ - А. М. Шилов; А. О. Осия (Архивъ внутренней медицины, 2012)
The authors present their experience of clinical observation and treatment of 42 patients with chronic heart failure (CHF) in combination with irondeficiency anemia (IDA) using iron supplements for parenteral (iron karboksimaltozat — 7 patients) and oral (Ferlatum — 42 patients) use. The role of IDAin the formation of the severity of CHF functional class was studied. It is shown that iron supplementation are clinically effective in treatment of chronic heart failure: with an increase in serum iron at 97.7% level of the hemoglobin (Hb) increased by 15.4%, left ventricle ejection fraction — by 32.2%, which allowed almost in 100% to reduce functional class of CHF. Inclusion of Ferlatum in the treatment program for CHF provides clinically necessary recovery in Hb (110–120 g/l) at IDA with minimum side effects.